Investigation of ultrasonic atomization to enhance performance of a micro jet engine using biofuel - Alajmi, Amer E. S. E. Th. (2019)
A jet engine is commonly used in aeronautical applications such as civilian airplanes, armed fighters, and helicopters, as it is one of the types of the gas turbine engine. Air enters through the compressor and injected into the combustion chamber to be mixed with fuel under pressure for combustion. This releases the energy of the heat to expand the volume of hot fluids and impact to the turbine wheel and generate the power of the hot gases. Such engines require tremendous amount of biodiesle. The ultrasonic atomization has been applied in different areas and shows positive potential performance. However, this promising atomizer technology has not yet applied in the micro jet engine to use biodiesel blends fuels. This gap in previous studies gave the motivation to investigates the potential of using ultrasonic atomization technology to assist the combustion process as a contribution for promising an alternative to the normal fuel atomization system. Firstly the new combustion equation is developed and validated, followed by determination of optimum conditions for combustion performance including optimum size of ultrasonic droplets. An experimental rig was set up to determine the performance of jet engine using ultrasonic droplets. The four- component set of ultrasonic atomizer devices delivers the fuel through the jet engine intake area, each device can deliver a 5 liter/ hour. The air mass flow was measured using a hot wire anemometer with speed limit 30 m/s fixed in front of the intake area. A load cell was installed to measure the actual thrust from the engine in units kgf. A gas analyzer was used to measure oxygen percentage, carbon monoxide, carbon dioxide and unburned hydrocarbons (uHC), nitrogen monoxide and nitrogen dioxide of the exhaust gas. The performance of the engine was tested under three levels of load (high, medium, low) starting from 10-psi at steady state to the minimum value. A significant result has been tested for a low value of nitrogen monoxide at the three levels of load, a specific result has been tested for efficiency value of 2% at the three levels of load, carbon dioxide is decreasing at the low level of load. The use of the ultrasonic atomization device to assist in the combustion process was useful in achieving engine efficiency of 1% of the micro jet performance and the reduce the emission of carbon dioxide exhaust gas to almost 25%.